Intercalated Iron Chalcogenides: Phase Separation Phenomena and Superconducting Properties - Krzton-Maziopa, Anna (Frontiers in Chemistry, 2021)
Layered iron-based monochalcogenides intercalated with organic molecules ungdergo intense research due to their fascinating magnetic and superconducting properties linked to the chemical nature of guests in the structure. Their ability for hosting various organic molecules between the weakly bound inorganic layers opens the possibility for fine tuning magnetic and electrical properties of intercalated phases by controlling both the doping level and the type/shape and orientation of the organic molecules. Recent years have brought significant progress in the area of intercalation chemistry, expanding the gallery of intercalated superconductors with new hybrid inorganic-organic phases characterized by transition temperatures to superconducting state as high as 46K. Typical synthetic approach involves low-temperature intercalation of layered precursors in the presence of liquid amines, and other methods, such as electrochemical intercalation, intercalant or ion exchange and direct solvothermal growths from anhydrous amine-based media are also being developed. Large organic guests, while entering the layered structure on intercalation, push off the inorganic slabs and modify geometry of their internal building blocks through chemical pressure. Both the chemical nature and orientation of organic molecules between the inorganic layers play important role in structural modification and may serve as a tool for alteration of superconducting properties. Variety of donor species well-matched with selected alkali metals enables adjustment of electron doping in host structure offering broad range of new materials with tunable electric and magnetic properties .Here the main aspects of intercalation chemistry are discussed, involving the influence of chemical and electrochemical nature of intercalating species on the crystal structure and critical issues related to superconducting properties of the hybrid inorganic-organic phases. Brief description of the most effective chemical and electrochemical methods leading to preparation of nano/microsized powders and single crystals of molecularly intercalated phases with critical assessment associated with the ease of preparation of phase pure materials, crystal sizes and morphology of final products is given together with discussion of stability of intercalated materials connected with volatility of organic solvents and possible degradation of host materials.